Marketing Communication Strategy for Millennial Farmers of Yogyakarta Special Region through Social Media - Ririn Puspita Tutiasri; Kusumajanti; Dian Hutami Rahmawati; Jonathan Diven Setiawan; Pandu Tanoyo (Future Science, 2022)
Millennial farmers from the Special Region of Yogyakarta (DIY) take advantage of social media as a marketing communication strategy for agricultural products. DIY millennial farmers focus on three fields, namely, food crop agriculture, animal husbandry, and horticulture. The products they produce are very diverse, including organic plants, vegetables, fruits, ornamental plants, quality livestock, and processed agricultural products. Many millennial farmers produce quality crops and livestock or experience an increase compared to the results produced by reliable farmers. Millennial farmers are farmers aged 19-39 years, and those aged above 39 are called reliable farmers. They also package processed agricultural products more attractively and can last longer. Social media is used as a means of communicating with extension workers, and fellow millennial farmers or to introduce products produced by millennial farmers using marketing communication strategies in cyberspace. Millennial farmers are part of the information society, they use communication media to support the development process. The purpose of this study is to describe the marketing communication strategy of agricultural products carried out by millennial farmers using various types of social media platforms. This study, uses a qualitative descriptive research method by conducting interviews with millennial farmers from Bantul, Sleman, Kulonprogo, Kota, and Gunungkidul. The results of this study indicate that farmers use social media social networks and media sharing to market their agricultural products.